We were liars [compact disc, unabridged] - Lockhart, E. (Listening Library, Random House, LLC, 2014)
Spending the summers on her family's private island off the coast of Massachusetts with her cousins and a special boy named Gat, teenaged Cadence struggles to remember what happened during her fifteenth summer.